The Dual Role of CCR5 in the Course of Influenza Infection: Exploring Treatment Opportunities - Ferrero, Maximiliano Ruben; Tavares, Luciana Pádua; Garcia, Cristiana Couto (Frontiers in Immunology, 2022)
Influenza is one of the most relevant respiratory viruses to human health causing annual epidemics, and recurrent pandemics. Influenza disease is principally associated with inappropriate activation of the immune response. Chemokine receptor 5 (CCR5) and its cognate chemokines CCL3, CCL4 and CCL5 are rapidly induced upon influenza infection, contributing to leukocyte recruitment into the airways and a consequent effective antiviral response. Here we discuss the existing evidence for CCR5 role in the host immune responses to influenza virus. Complete absence of CCR5 in mice revealed the receptor’s role in coping with influenza via the recruitment of early memory CD8+ T cells, B cell activation and later recruitment of activated CD4+ T cells. Moreover, CCR5 contributes to inflammatory resolution by enhancing alveolar macrophages survival and reprogramming macrophages to pro-resolving phenotypes. In contrast, CCR5 activation is associated with excessive recruitment of neutrophils, inflammatory monocytes, and NK cells in models of severe influenza pneumonia. The available data suggests that, while CCL5 can play a protective role in influenza infection, CCL3 may contribute to an overwhelming inflammatory process that can harm the lung tissue. In humans, the gene encoding CCR5 might contain a 32-base pair deletion, resulting in a truncated protein. While discordant data in literature regarding this CCR5 mutation and influenza severity, the association of CCR5delta32 and HIV resistance fostered the development of different CCR5 inhibitors, now being tested in lung inflammation therapy. The potential use of CCR5 inhibitors to modulate the inflammatory response in severe human influenza infections is to be addressed